Microbiologically Influenced Corrosion Testing 1994
DOI: 10.1520/stp12936s
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Microbiologically and Chemically Influenced Corrosion of Natural Sandstone

Abstract: A test system for the simulation of a combined chemically (gaseous pollutants) and microbiologically (nitrifying bacteria) influenced corrosion on natural sandstone is presented. A high stone moisture was essential for the growth of nitrifying bacteria on test stones. Under optimum conditions, a nitrifying biofilm developed on the calcareous Ihrlersteiner green sandstone, reducing the evaporation from the stone surface. Biofilm cells adapted well to high concentrations of gaseous pollutants. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Growth of nitrifying organisms on concrete is not sequential as observed for the sulfur-oxidizing bacteria. However, in controlled experiments (using a simulation chamber), it was found that mixed cultures of Nitrosomonas and Nitrobacter inoculated on concrete blocks produced about 14 mL of 65% nitric acid per block per year (Mansch and Bock 1992). This was sufficient acid to dissolve the concrete and produce the breakdown product calcium nitrate.…”
Section: Technical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth of nitrifying organisms on concrete is not sequential as observed for the sulfur-oxidizing bacteria. However, in controlled experiments (using a simulation chamber), it was found that mixed cultures of Nitrosomonas and Nitrobacter inoculated on concrete blocks produced about 14 mL of 65% nitric acid per block per year (Mansch and Bock 1992). This was sufficient acid to dissolve the concrete and produce the breakdown product calcium nitrate.…”
Section: Technical Backgroundmentioning
confidence: 99%
“…1993). However, data from the literature (Diercks et al 1991;Mansch and Bock 1992) indicate that these bacteria do grow on the surface of concrete under natural and laboratory conditions. The question of how to initiate growth on fresh concrete was answered by Bock.…”
Section: Nureg/cr-6188mentioning
confidence: 99%
“…Microbial involvement in the biodegradation of concrete has been studied extensively (Jozsa et al 1996;Mansch and Bock 1994).…”
Section: Introductionmentioning
confidence: 99%